Nanocurcumin Potential Effect of SOD Enzyme and Caspase-3 Expression in Lead-Acetate Induced Rats Ovarian Granulosa Cells - Anis Satus Syarifah; Sri Agus Sudjarwo; Hendy Hendarto; Reny I’tishom; Supriyanto (Indian Journal of Forensic Medicine & Toxicology, 2021)
Aim: This study investigated the potential effect of nanocurcumin on the increase of SOD enzyme expressionand decrease of caspase-3 in lead acetate-induced rats ovarian granulosa cells.Materials and Methods: Forty five female rats were divided into 5 groups, the negative control group (ratsreceiving corn oil, one hour later receiving distilled water), positive control group (rats receiving corn oil,one hour later receiving lead acetate of 40 mg/kg bw) and experimental groups 1, 2 and 3 (rats receivingnanocurcumin 50 mg, 100 mg and 200 mg/kg bw). One hour after administering the nanocurcumin, therats received 40 mg/kg of lead acetate. All groups received oral treatment once a day for 26 days. Onday 27 the rats were sacrificed and the expression of SOD and caspase-3 enzymes were measured usingimmunohistochemical methods.Results: This study found that lead acetate decreased SOD enzyme expression and increased caspase-3. Incontrast, nanocurcumin increased SOD enzyme and decreased caspase-3 expression in lead acetate-inducedrats ovarian granulosa cells.Conclusion: Nanocurcumin has potential as a strong natural antioxidant by affecting the increase of SODand the decrease of caspase-3 cells in lead acetate-induced rats ovarian granulosa cells.